2010
DOI: 10.1021/bi9022285
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive NADPH-Dependent Electron Transferase Activity of the Nox4 Dehydrogenase Domain

Abstract: NADPH oxidase 4 (Nox4) is constitutively active, while Nox2 requires the cytosolic regulatory subunits p47phox and p67phox and activated Rac with activation by phorbol 12-myristate 13-acetate (PMA). This study was undertaken to identify the domain on Nox4 that confers constitutive activity. Lysates from Nox4-expressing cells exhibited constitutive NADPH- but not NADH-dependent hydrogen peroxide production with a Km for NADPH of 55 ± 10 μM. The concentration of Nox4 in cell lysates was estimated using Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(131 citation statements)
references
References 58 publications
(98 reference statements)
5
124
1
1
Order By: Relevance
“…Using two different methods of protein synthesis, we demonstrate that the cytosolic domain of Nox4 is responsible for Nox4 constitutive activity. Other authors using a similar portion of the C-terminal part of Nox4 have made the same observations [26,27].…”
Section: Diaphorase Activity Of Nox4 Truncated Proteinssupporting
confidence: 60%
“…Using two different methods of protein synthesis, we demonstrate that the cytosolic domain of Nox4 is responsible for Nox4 constitutive activity. Other authors using a similar portion of the C-terminal part of Nox4 have made the same observations [26,27].…”
Section: Diaphorase Activity Of Nox4 Truncated Proteinssupporting
confidence: 60%
“…Second, several recent independent reports indicate that Nox4 generates predominantly H 2 O 2 (as further confirmed in the current study) whereas Nox2 primarily generates O 2 − (refs. [17][18][19][20]. These differences in regulation, activation mechanism, subcellular location, and ROS generation translate into isoform-specific actions in isolated cellular models (9,19,22,33).…”
Section: Discussionmentioning
confidence: 99%
“…Nox4 differs from Nox2 and other Nox enzymes in that it is regulated mainly by its expression level and does not require agonist stimulation or association with regulatory subunits for activation (16)(17)(18). Recent studies also suggest that it generates predominantly H 2 O 2 rather than O 2 − (17)(18)(19)(20). Previous work showed that Nox4 is expressed at a low level in the adult mammalian heart and that its abundance increases during pressure overload (11), but its pathophysiological functions in vivo are unknown.…”
mentioning
confidence: 99%
“…However, two partners of Nox4 have been described recently: the protein disulfide isomerase (PDI) and the polymerase DNA directed-delta-interacting protein (Poldip2). Nox4 is unique among other Nox isoenzymes in that its activity is constitutive and may depend on a specific conformation of the dehydrogenase DH domain that should allow a spontaneous transfer of electrons from NADPH to FAD and to the hemes [24,25]. Data from various studies indicated clearly that Nox4 activity is regulated at the mRNA level, implying that an increase or decrease of ROS production by Nox4 is correlated to an up regulation [9,16,[26][27][28][29][30][31][32][33] or to a decline [34] of Nox4 transcripts.…”
Section: Introductionmentioning
confidence: 99%